Paradoks Penanganan Stunting: Studi Kasus Lonjakan Angka Stunting di Kecamatan Mendo Barat di Tengah Rekognisi Keberhasilan Penurunan Stunting di Kabupaten Bangka - Muhammad Badawi Almuarrof; Rangga Juwanda Sapitra; Alif Rizki Wahyudi; Eko Saputra; Irvan Ansyari (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Study examines the paradox between the awards received by Bangka Regency at the local and national levels for stunting reduction and the actual condition in Mendo Barat District, which has continuously been designated as a stunting locus from 2019 to 2024. Research employs Michael Lipsky’s (1980) Street-Level Bureaucracy theory and uses a qualitative method with a case study approach conducted between 2020 and 2024.Findings indicate that the paradox arises because coordination among coordinators, field officers, and communities has not been fully aligned due to limited resources. These constraints trigger the emergence of discretionary practices and coping mechanisms. The main strategic error lies in the excessive focus on children already affected by stunting, rather than emphasizing preventive measures. Programs implemented tend to focus on short-term reduction efforts rather than holistic prevention. Consequently, this situation creates an imbalance between the recognition received by the government and the actual field conditions in Mendo Barat District. In addition, program implementation varies across the area, leading to different interpretations at the local level and reducing overall program effectiveness. The direction of policy implementation should not depend solely on the government or field officers, but also on the active role of the community. Community participation, particularly among families affected by stunting, remains passive limited to being program beneficiaries rather than active agents in addressing stunting issues. For example, the low adoption of the GERMAS principles in daily life such as hygiene behavior, healthy lifestyles, and dietary ethicsillustrates this challenge, as emphasized in PERBUP No. 56 of 2022.